C.1 - "Kaul, T. N." (New Delhi, 1988)
This book covers following topics: Foreign policy; the commonwealth; India's foreign policy; Foreign policy goals; grasshopper diplomacy ; India and neighbours; peace and security; post independence foreign relations; Diplomacy, diplomats, government and people etc.
Keywords: India foreign relations